Analisis Penentuan Pusat-Pusat Pertumbuhan Ekonomi Kota Bengkulu - As'Ad; Ellya Revolina; Ozi Rahmat Putra (Pencerah, 2023)
This research aims to determine which sub-districts that becomes the centers of economic growth in Bengkulu City, and how big is the interaction between the growth of the center sub-district economic and the sub-districts in the surrounding area. This research uses secondary data in 2021 sourced from BPS Bengkulu Province, BPS of Bengkulu city, along with journals and literature related to this research. The data analysis method that is used in this study is Scalogram Analysis by combining the Centrality Index and weighting techniques and Gravity Analysis. Scalogram analysis is used to determine the centers of economic growth in each sub-district based on the availability of public service facilities such as government facilities, economic facilities, and social facilities. Gravity analysis is used to find out how much interaction is between the sub-districts economic growth and the surrounding sub-districts (hinterland) by using the variable of population and the distance between the two regions. Based on the results of the research from the Scalogram Analysis and the centrality index that has been carried out, that the growth center in Bengkulu City is based on 30 service facilities, which is Bengkulu city with the highest total service facilities and centrality index. Based on the results of gravity analysis using population and distance variables of the central district of Central Bengkulu has the strongest interaction with Singaran Pati District as the surrounding area (hinterland).